Mediation in the Multicultural Society of Kazakhstan: Tradition and Modernity - ABIYEV, Y.M.; SHERYAZDANOVA, G.R.; BYULEGENOVA, B.B.; RYSTINA, I.S.; GABDULINA, B.A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Mediation is considered as a form of pre-trial conflict settlement as exemplified by both modern mediation councils and traditional mediation institutions in Kazakhstan. The paper considered the multiculturalism as a nation-building liberal theory that seeks the equality rights of ethnic minorities within one civic identity. Based on the analysis of the Multiculturalism Policy Index of Kazakhstan (MPI), a conclusion is drawn on the level of compliance with the rights of ethnic groups in Kazakhstan. The article investigated empirical data of the recent inter-ethnic conflicts in southeastern Kazakhstan that are used to analyze the problems and methods of resolving inter-ethnic conflicts. RESUMEN La mediación se considera como una forma de solución de conflictos previa al juicio, como lo demuestran los consejos de mediación modernos y las instituciones de mediación tradicionales en Kazajstán. El documento consideraba el multiculturalismo como una teoría liberal de construcción de la nación que busca los derechos de igualdad de las minorías étnicas dentro de una identidad cívica. Basado en el análisis del Índice de Políticas de Multiculturalismo de Kazajstán (IPM), se llega a una conclusión sobre el nivel de cumplimiento de los derechos de los grupos étnicos en Kazajstán. El artículo investigó datos empíricos de los recientes conflictos interétnicos en el sureste de Kazajstán que se utilizan para analizar los problemas y métodos para resolver conflictos interétnicos.